Interactions between the sexual identity of the nervous system and the social environment mediate lifespan in Drosophila melanogaster. Issue 1892 (28th November 2018) - Flintham, Ewan O.; Yoshida, Tomoyo; Smith, Sophie; Pavlou, Hania J.; Goodwin, Stephen F.; Carazo, Pau; Wigby, Stuart
Abstract : Sex differences in lifespan are ubiquitous, but the underlying causal factors remain poorly understood. Inter- and intrasexual social interactions are well known to influence lifespan in many taxa, but it has proved challenging to separate the role of sex-specific behaviours from wider physiological differences between the sexes. To address this problem, we genetically manipulated the sexual identity of the nervous system—and hence sexual behaviour—in Drosophila melanogaster, and measured lifespan under varying social conditions. Consistent with previous studies, masculinization of the nervous system in females induced male-specific courtship behaviour and aggression, while nervous system feminization in males induced male–male courtship and reduced aggression. Control females outlived males, but masculinized female groups displayed male-like lifespans and male-like costs of group living. By varying the mixture of control and masculinized females within social groups, we show that male-specific behaviours are costly to recipients, even when received from females. However, consistent with recent findings, our data suggest courtship expression to be surprisingly low cost. Overall, our study indicates that nervous system-mediated expression of sex-specific behaviour per se —independent of wider physiological differences between the sexes, or the receipt of aggression or courtship—plays a limited role in mediating sex differences in lifespan.